Model Kooperatif Make A Match untuk Meningkatkan Hasil Belajar dan Aktivitas Belajar IPS Siswa Kelas IV - Ernawati Ernawati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
The low learning achievement and learning activities of the fourth grade students at SDN 17 Nan Sabaris Kabupaten Padang Pariaman for Social subject was an effect of the traditional learning. This research was aimed to improve the learning achievement and learning activities of the fourth grade students at SDN 17 Nan Sabaris Kabupaten Padang Pariaman by implementing the Make a Match learning model. Data of research were obtained through observation and post test. Data of research were analyzed quantitatively and qualitatively. In cycle I, percentage of students’ learning achievement is 61,70% and becomes 73,52% in cycle II. Meanwhile, the percentage of students’ learning activity is in cycle I is 63,11% and becomes 80,81% in cycle II. The result of research shows that implementation of Make a Match learning model can improve learning achievement and learning activities of the fourth grade students at  IV SDN 17 Nan Sabaris Kabupaten Padang Pariaman.